Thymoquinone Selectively Induces Hepatocellular Carcinoma Cell Apoptosis in Synergism With Clinical Therapeutics and Dependence of p53 Status - Jehan, Shah; Zhong, Chen; Li, Guangyue; Zulqarnain Bakhtiar, Syed; Li, Dangdang; Sui, Guangchao (Frontiers in Pharmacology, 2020)
Thymoquinone (TQ) is a natural compound extracted from the black seeds of Nigella sativa Linn. belonging to the Ranunculaceae family. TQ exhibits anti-inflammatory and antineoplastic activities against various cancers. Many therapeutics in hepatocellular carcinoma (HCC) treatments, such as doxorubicin (DOX) and cisplatin (DDP), exhibit considerable side effects on patients. We investigated cytotoxic effects of TQ, alone or in combination with DDP and DOX to HCC cells. TQ exhibited selective killing to HCC HepG2 and SMMC-7721 cells, but relatively low toxicity to normal liver HL-7702 cells. Importantly, when used with DOX or DDP, TQ showed synergistic inhibition of HCC cells, but not HL-7702 cells. We also discovered that Hep3B cells with a p53 null status were more sensitive to TQ than HepG2 and SMMC-7721 cells harboring wild type p53. Consistently, shRNA-mediated p53 silencing in HepG2 cells dramatically enhanced TQ-induced apoptosis, measured by caspase 3 and PARP cleavage. Furthermore, TQ-stimulated increase of reactive oxygen species (ROS) in p53-depleted cells was more pronounced than that in cells with intact p53. In summary, we discovered that TQ synergistically improves the anticancer activity of DOX and DDP, and loss of p53 sensitizes HCC cells to TQ-induced apoptosis.